Analysis of the training, self-perception and information competence of young people in Spain in internet search strategies / Análisis de la formación, autopercepción y competencias informacionales de los jóvenes españoles sobre sus estrategias de búsqueda en Internet - Beriain-Bañares, Ana; de Vicente-Domínguez, Aida-María; Sierra-Sánchez, Javier (Culture & Education / Cultura y Educación, 2025)
European guidelines have stressed the urgent need to train citizens in competencies related to the search for information on the internet, and this study offers, for the first time, an overview of the information literacy of young people in Spain aged between 18 and 25. The objectives are: to learn what training they have received and their interest in learning; to investigate their self-perception; and to analyse their search skills. The method consists of a descriptive quantitative study in which a structured questionnaire was administered to a representative sample of the population studied (n = 500), with a sampling error of ± 4.47% and a confidence level of 95%. The data are weighted according to socio-demographic variables (gender, age, level of education, social class, habitat size and geographical area) to analyse whether there are statistically significant differences using the chi-squared test. The results indicate that in this area, they have not been trained, are self-taught and, although they believe they know how to search on the internet, do not know how and where to search beyond a beginner's level. It is concluded that this population is failing in this information competence and that there is a digital divide that needs to be bridged as a matter of urgency.